The influence of Investment Efficiency on Financial Performance - Azzahra Kurnia Fitri; Fenny Marietza (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this research is to see how investment efficiency can increase profitability. This research was conducted as a from of population gap seen in previos studies, so this study aims to re-examine the effect of investment efficiency on finansial performance. The novelty inthis research is to analyze the direct influence between investment efficiency on financial performance. This research uses a quantitative approach with secondary data. The population of this study is companies indexed LQ45 in the 2018-2022 period, the sample of this study is 27 companies with 135 observation that meet the criteria. This research was tested using multiple linear regression analyze using the Eviews application with the result that investment efficiency cannot affect financial performance